Uso de substâncias psicoativas na gestação - Ferreira, Uly Reis (2024)
This research aimed to analyze the prevalence, associated factors, and understand the repercussions of psychoactive substance use during pregnancy, viewed through the lens of Social Ecological Theory. It is a mixed-methods study with data triangulation, conducted in two public maternity hospitals in Fortaleza, Ceará. The study took place from November 2023 to June 2024, involving 403 postpartum women who completed the quantitative survey and 15 psychoactive substance users who participated in the qualitative phase. Inclusion criteria for the quantitative phase were postpartum women admitted to the maternity ward, with 12 hours postpartum, aged over 18. Exclusions applied to those with physical or psychological limitations preventing questionnaire responses. For the qualitative phase, women who had used psychoactive substances during pregnancy participated, while those in abstinence were excluded. Data analysis was conducted using the Statistical Package for the Social Sciences. Qualitative data were analyzed using Reflexive Thematic Analysis, structured into six stages: 1) Familiarization with data; 2) Generating initial codes; 3) Searching for themes; 4) Reviewing themes; 5) Defining and naming themes; and 6) Report writing. Four key themes emerged: Support Networks and External Influences, Perception of Drug Use and Consequences, Patterns of Drug Use in the Perinatal Cycle, and Health Care. The study was approved by the Ethics Committee of the Federal University of Ceará, under number 6.527.091, with all ethical and legal requirements of the National Health Council adhered to. Participants' ages ranged from 18 to 45 years, with most living with a partner (65.5%), identifying as mixed-race (73.2%), from the capital of Ceará (80.6%), and unemployed (62%). Among the participants, 9.2% reported psychoactive substance use, with tobacco having the highest prevalence (64.9%), followed by alcohol (45.9%), cocaine (27%), and marijuana (24.3%). Most tobacco users reported daily use (27%), while alcohol was used occasionally (21.6%) and marijuana weekly (10.8%). Associated factors included having up to 9 years of education, having a substance-dependent partner, support network, and having undergone socioeducational measures or imprisonment. In the qualitative analysis, participants noted that while support is sometimes present, it is often insufficient to promote effective behavioral changes. Moreover, the presence of other users can intensify the desire for drug use. Feelings of guilt and regret were linked to concerns about fetal health. Physical changes during pregnancy might reduce substance use, but the lack of information and external support, as well as the absence of help-seeking behavior, indicated possible gaps in motivation or access to support resources. It is concluded that the prevalence of psychoactive substance use among pregnant women was significant. Social and structural factors were directly associated with substance use, underscoring the urgency for more inclusive public policies that promote equity in care.